Regeneração natural em floresta estacional decidual aluvial: fisionomia, espécies potenciais para restauração ecológica e variáveis ambientais - Dick, Grasiele (2014)
This study was conducted in an area of Stational Deciduous Alluvial Forest, which was abandoned and isolated, located in the Colônia State Park in the municipality of Agudo, Rio Grande do Sul State, Brazil. The main objective was to analyze the physiognomy and the influence of environmental variables, in order to assess the dynamics in the forest during a year (2011-2012) and to identify potential species for ecological restoration. This dissertation was divided in two studies, with specific goals to characterize the forest in terms of floristic composition, ecology, structure, dynamics and group formations (Study 1), and the characterization of morphological, chemical and physical variables of the soil, and their relationships with the vegetation distribution (Study 2). To this end, 19 sampling units were allocated, with dimensions of 10 m x 10 m, in which the vegetation was sampled in four classes of inclusion (Regeneration 1 = DAS ≤ 1 cm; Regeneration 2 = 1 cm ≤ CAP ≥ 5 cm; Arboreal 1 = 5.1 cm ≥ CAP ≤ 14.9 cm; Arboreal 2 = CAP ≥ 15 cm), also where environmental variables were characterized. In the floristic composition, 63 species were identified belonging to 27 families and seed dispersal of zoochory type. The highest diversity was observed in the smallest classes of inclusion (R1 and R2), as well as the greater number of individuals and significant occupation by exotic species. Changes occurred in the community throughout the year, with evidences of the succession process of species, especially the Asteraceae and Escallonia bifida families. The mortality rate (9.5%) was higher than then recruitment rate (6.3%). The Two-Way Indicator Species Analysis revealed the species Sebastiania commersoniana, Eugenia uniflora, Myrsine umbellata and Asteraceae family as natural regeneration indicators, and Escallonia bifida, Jacaranda micrantha and Eugenia uniflora as indicators of the arboreal stratum. Along with Casearia sylvestris, Allophyllus edulis, Prunus myrtifolia and Matayba elaeagnoides, such species were also significant in the phytosociological analysis, characterizing forest occupation and succession in the area. The soil in the sampling area is classified as Fluvic Neosol and sandy eutrophic Haplic Planosol. The soil showed high fertility and physical features characteristic of past agricultural use. Using a pre analysis of the principal component, the most significant species and variables were related by means of the Canonical Correspondence Analysis, which showed that the species are distributed on the basis of chemical variation considering P, Ca, Al, pH, base saturation, CTC and soil resistance to penetration.